Cardiorespiratory Fitness and Body Mass Index as Predictors of Metabolic Syndrome in Schoolchildren (PACH Study) - Raudeniece J; Justamente I; Ozolina-Moll L; Sobolevs A; Zolovs M; Dela F; Reihmane D (Diabetes, Metabolic Syndrome and Obesity)
Jelena Raudeniece,1– 3 Ilze Justamente,1– 3 Liga Ozolina-Moll,1 Artjoms Sobolevs,4 Maksims Zolovs,5,6 Flemming Dela,2,7 Dace Reihmane2,3 1Department of Human and Animal Physiology, Faculty of Biology, University of Latvia, Riga, Latvia; 2Department of Human Physiology and Biochemistry, Riga Stradiņš University, Riga, Latvia; 3Laboratory of Sports and Nutrition Research, Riga Stradiņš University, Riga, Latvia; 4Department of Pathology, Faculty of Medicine, Riga Stradiņš University, Riga, Latvia; 5Statistics Unit, Riga Stradiņš University, Riga, Latvia; 6Institute of Life Sciences and Technology, Department of Biosystematics, Daugavpils University, Daugavpils, Latvia; 7Xlab, Department of Biomedical Sciences, Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Jelena Raudeniece, Department of Human and Animal Physiology, Faculty of Biology, University of Latvia, Jelgavas Street 1, LV-1004, Riga, Latvia, Email jelena.raudeniece@olimpiade.lvPurpose: Metabolic syndrome (MetS) has become a condition not rarely diagnosed in children and adolescents, leading to changes in physical and mental health. Simple and cost-effective screening methods applied in schools are needed to take preventive measures and reduce the risk of the development of MetS in children.Methods: This prospective longitudinal study aims to investigate the prevalence of MetS and its risk factors in 8– 10-year-old schoolchildren (46 boys and 60 girls) over 3 consecutive years. General Linear Mixed Model (GLMM) was used to assess the effect of recommended daily levels of moderate to vigorous physical activity (MVPA), body mass index (BMI), waist circumference (WC), cardiorespiratory fitness (CRF), and obesity level on a new set of orthogonal variables formed from various parameters of MetS (eg blood pressure (BP), lipid panel and glucose homeostasis) determined by Principal Component Analysis (PCA).Results: The prevalence of MetS was 2% in the years 2017, 2018 and 2019, while in 2020 prevalence reached 7.7%. The most prevalent combination of criteria defining MetS syndrome in children was increased WC, BP, and blood triglycerides (TG). PCA identified non-high-density lipoprotein (non-HDL), low-density lipoprotein (LDL), and total cholesterol (TCHOL) as important predictors of metabolic syndrome (MetS). Additionally, cardiorespiratory fitness (CRF) and body mass index (BMI) were found to significantly influence the variance in MetS criteria. However, moderate to vigorous physical activity (MVPA) did not have a notable effect on the variance of these criteria.Conclusion: The prevalence of MetS in children is increasing with age. Non-HDL turned out to be the most influential parameter across all principal components. The CRF, being accessible, simple to use, non-invasive and cost-effective, proved to be a superior predictor of variance of glucose homeostasis compared to BMI.Keywords: cardiorespiratory fitness level, cardiometabolic health, BMI, MVPA, pupils